The Personality of Sultan Baybars and His Role in Developing Relations of the Mamluk Egypt with the Golden Horde according to Arab Sources - Sayfetdinova E.G. (Золотоордынское обозрение)
Objective: To consider the personality of the Mamluk Sultan Baybars and his role in developing relations with the Golden Horde. Research materials: The medieval Arabic chronicles of Sultan Baybars’ first biographers, Abd al-Zahir and Ibn Shaddad, as well as the information of later authors – Rukn al-Din Baybars, al-Maqrizi, al-Nuwayri, al-Ayni, and others. Results and novelty of the research: It is known that close relations with Berke Khan of the Golden Horde were developed during the reign of Sultan Baybars. The purpose of this alliance was the desire to neutralize the role of the Hulaguid state in the international arena. The fact that Baybars was of Kipchak origin was an important contributor to friendly relations. Despite the different information of medieval Arab authors regarding which original clan Baybars belonged to, we can quite definitely say that Baybars originated from the Barli tribe, based on the information of his main biographer Abd al-Zahir. The person of Baybars left its mark not only in the history of Mamluk Egypt, but also in the global historical context of the Muslim world. Both the promotion of their political interests and the preservation of cultural identity played an important role in the interrelations of Baybars with Berke Khan of the Golden Horde.